Cri-du-chat syndrome: application of array CGH in diagnostic evaluation - Zarina AL,; Juriza I,; Sharifah Azween SO,; Azli I,; Mohd Fadly MA,; Zubaidah Z,; Chia WK,; Clarence Ko CH,; Julia MI,; Khairunisa K,; SSSSharifah Noor Akmal SH, (Penerbit UKM, 2010)
The human genome contains many submicroscopic copy number variations which includes deletions, duplications and insertions. Although conventional karyotyping remains an important diagnostic tool in evaluating a dysmorphic patient with mental retardation, molecular diagnostic technology such as array comparative genomic hybridization (aCGH) has proven to be sensitive and reliable in detecting these submicroscopic anomalies. A 3 month-old infant with dysmorphic facies, microcephaly and global developmental delay was referred for genetic evaluation. Preliminary karyotyping which was confounded by the quality of metaphase spread was normal; however, aCGH detected a 30.6Mb deletion from 5p15.33-p13.3. This case illustrates the usefulness of aCGH as an adjunctive investigative tool for detecting chromosomal imbalances.